Behavioral and transcriptomic effects of the cancer treatment tamoxifen in mice - Galvano, Elena; Pandit, Harshul; Sepulveda, Jordy; Ng, Christi Anne S.; Becher, Melanie K.; Mandelblatt, Jeanne S.; Van Dyk, Kathleen; Rebeck, G. William (Frontiers in Neuroscience, 2023)
Tamoxifen is a common treatment for estrogen receptor-positive breast cancer. While tamoxifen treatment is generally accepted as safe, there are concerns about adverse effects on cognition. Here, we used a mouse model of chronic tamoxifen exposure to examine the effects of tamoxifen on the brain. Female C57/BL6 mice were exposed to tamoxifen or vehicle control for six weeks; brains of 15 mice were analyzed for tamoxifen levels and transcriptomic changes, and an additional 32 mice were analyzed through a battery of behavioral tests. Tamoxifen and its metabolite 4-OH-tamoxifen were found at higher levels in the brain than in the plasma, demonstrating the facile entry of tamoxifen into the CNS. Behaviorally, tamoxifen-exposed mice showed no impairment in assays related to general health, exploration, motor function, sensorimotor gating, and spatial learning. Tamoxifen-treated mice showed a significantly increased freezing response in a fear conditioning paradigm, but no effects on anxiety measures in the absence of stressors. RNA sequencing analysis of whole hippocampi showed tamoxifen -induced reductions in gene pathways related to microtubule function and synapse regulation. Overall, these findings of the effects of tamoxifen exposure on fear conditioning and on gene expression related to neuronal connectivity suggest that there may be CNS side effects of this common breast cancer treatment.